Situation of Turkey The 1920 Revolution in Iraq (History Study) - حامد محمد طه السويداني, أ. م. د (lark, 2020)
Abstract:The research talks about the Twentieth Revolution in Iraq, focusing on its importance and universality, reading its events with a new analytical vision as one of the most significant events in the history of Iraq and the fact that it directly contributed to the establishment of the Iraqi State in 1921. The research was divided into two themes: the first one is "the Twentieth Revolution (Reasons and Results)". The second theme is the attitude of the Turks to the Twentieth Revolution in Iraq; it is supported by Ottoman documents. The research concluded a set of important conclusions and treatments.
Keywords: Revolution, Iraq, Turks, Occupation, Twentieth, British